Length-weight relationship, condition factor and cannibalism in Asian seabass Lates calcarifer (Bloch, 1790) reared in nursery - Kumar, Prem; Kailasam, M.; Mahalakshmi, P.; Borichangar, R. V.; Vanza, G. J.; Gopal, C. (Indian Journal of Fisheries, 2016)
The length-weight relationship of Asian seabass Lates calcarifer (Bloch, 1790) reared in net cage hapa was studied for a period of 45 days. A total of 22,500 nos. of seabass fry (mean length 1.76 ± 0.39 cm; mean weight 0.132 ± 0.10 g) were stocked in fifteen hapas @ 1500 nos. per hapa (2x1x1m) and fed twice daily with farm made feed @ 10% of the body weight initially and reduced to 8% later on. Sampling was done at an interval of 15 days to assess the growth, survival, cannibalism and performance. On termination of the experiment, survival was 25%. Cannibalism contributed 11–51% to the total mortality. K value >1 indicated healthy condition of fish. During the entire culture period, growth was negatively allometric (b